1970
DOI: 10.1063/1.1658476
|View full text |Cite
|
Sign up to set email alerts
|

Extension of a Theory of Damping Due to Dislocations

Abstract: A theory of mechanical damping based on the model developed by Granato and LUcke was extended to small numbers of pinning points per network length and to streoses high enough to produce complete breakaway. The detailed response of a dislocation array to an applied stress was calculated using computer techniques in the low-frequency (kilocycle) range and both the viscous and hysteretic damping were computed. The amplitude dependence of the viscous and hysteretic damping was computed as a function of loop-lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1972
1972
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…However, in terms of protecting passengers or stored data from sudden accidents, impacts, noise, and irregular vibrations, the high damping characteristics of Mg alloys are also regarded as an important factor for their structural applications [4][5][6][7]. In the case of Mg alloys, it is generally difficult to obtain a combination of high strength and high damping capacity, because the damping mechanism is related to easy dislocation motion [8][9][10][11], whereas their hardening mechanisms usually involve grain refinement and dispersion of solutes, segregates, and secondary particles, which play a role in obstructing dislocation movement. In a previous work [12], it was reported that a small addition of Ca (~0.3%) to AM50 Mg alloy contributes to increasing its damping capacity.…”
Section: Introductionmentioning
confidence: 99%
“…However, in terms of protecting passengers or stored data from sudden accidents, impacts, noise, and irregular vibrations, the high damping characteristics of Mg alloys are also regarded as an important factor for their structural applications [4][5][6][7]. In the case of Mg alloys, it is generally difficult to obtain a combination of high strength and high damping capacity, because the damping mechanism is related to easy dislocation motion [8][9][10][11], whereas their hardening mechanisms usually involve grain refinement and dispersion of solutes, segregates, and secondary particles, which play a role in obstructing dislocation movement. In a previous work [12], it was reported that a small addition of Ca (~0.3%) to AM50 Mg alloy contributes to increasing its damping capacity.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Granato-Lücke (G-L) theory [1][2][3][4], the total damping capacity (δ) can be divided into strain-amplitude-independent (δ o ) and strainamplitude-dependent (δ H ) damping components. The δ o component is attributed to the loss caused by forced vibrations of dislocation segments pinned by weak pinning points, such as vacancies and solute atoms.…”
Section: Resultsmentioning
confidence: 99%
“…The δ H values were obtained from the tan φ values according to the formula δ = π tan φ [22]. A linear relationship was established between ln( δ H × ε ) and 1/ ε , which demonstrates that the damping of the solutionised and aged AZ91 alloys occurred according to the dislocation damping mechanism [1-4]. In Figure 5, ln( C 1 ) and C 2 correspond to the y -axis intercept and the slope, respectively; the obtained C 1 and C 2 values are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…division has some basis in theory, althoughas Trott and Birnbaum (1970) have emphasized, the amplitude independence of^breaks down with the onset of the disloca tion breakaway process that leads to the appearance of <^h.The first two sections deal with the theory and experiments related to <f>t, while the last two sections cover the same ground for <£h.…”
mentioning
confidence: 99%